Diplomasi oleh Pemerintah Kota: Dinamika Kerja Sama Kota Kembar antara Pemerintah Kota Bandung dengan Pemerintah Kota Liuzhou - Tiara Galuh Saraswati; Reni Windiani; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Bandung city government has legality as a sub-state actor in carrying out foreign cooperation. Currently, Bandung has fifteen partners in the city of sister city cooperation and one of them is Liuzhou City. Although it has been established for 15 years, several areas of cooperation have not yet been implemented. In addition, this cooperation has been in a vacuum for seven years. With this background, this research aims to determine why this cooperation did not run smoothly. This research uses qualitative methods with sources obtained from official documents and interviews. The result of this research is that cooperation does not run smoothly because three out of five key elements of cooperation between cities according to UNDP are not fulfilled. Which are commitment to link, community participation in the project, and reciprocity.